1970
DOI: 10.3329/cardio.v3i2.9197
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Severe Tricuspid Stenosis of Rheumatic Origin

Abstract: Tricuspid valve stenosis is a valvular heart disease which results in the narrowing of the orifice of the tricuspid valve of the heart. It’s relatively a rare condition. It is almost always caused by rheumatic fever and is generally accompanied by mitral stenosis.Other rare causes include carcinoid syndrome, endocarditis, endomyocardial fibrosis, lupus erythematosus, right atrial myxoma and congenital tricuspid atresia. Here we describe a patient with history of prior CMC presented with severe Tricuspid Stenos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…5,6 In Pakistan, previously multiple local studies and surveys addressed the overall patterns of RHD and association of different valvular disease, based on the examination of local communities or frequency and incidence in the hospital settings. 3,9,11,[15][16][17][18][19][20][21][22][23] The Fahim et al ( 2007) study results on 3060 RHD patients showed that 70% patients affected by MS followed by MR in 58.59% cases. 23 Similarly, the screening study by MA Shaikh et al on valvular lesions on 100 RHD patients, reported mitral stenosis (MS, 48%), followed by mitral regurgitation (MR, 42%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,6 In Pakistan, previously multiple local studies and surveys addressed the overall patterns of RHD and association of different valvular disease, based on the examination of local communities or frequency and incidence in the hospital settings. 3,9,11,[15][16][17][18][19][20][21][22][23] The Fahim et al ( 2007) study results on 3060 RHD patients showed that 70% patients affected by MS followed by MR in 58.59% cases. 23 Similarly, the screening study by MA Shaikh et al on valvular lesions on 100 RHD patients, reported mitral stenosis (MS, 48%), followed by mitral regurgitation (MR, 42%).…”
Section: Discussionmentioning
confidence: 99%
“…7,8 The condition is almost always related to rheumatic disease, may also associated with other rare conditions like endocarditis, Lupus erythematous, right atrial myoma, endomyocardial fibrosis and congenital tricuspid atresia. 9 Tricuspid stenosis can exist as a congenital lesion or present later in the life with other conditions. 10 Although, the contribution of the tricuspid valve is well recognized in Rheumatic https://doi.org/10.29309/TPMJ/2021.28.09.6100 patients, still the disorders of right-sided cardiac valves attract less attention than left-sided valves.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation